2018
DOI: 10.1016/j.jnucmat.2018.06.029
|View full text |Cite
|
Sign up to set email alerts
|

Modelling and experimental analysis of the effect of solute iron in thermally grown Zircaloy-4 oxides

Abstract: Simulations based on density functional theory (DFT) were used to investigate the behaviour of substitutional iron in both tetragonal and monoclinic ZrO 2. Brouwer diagrams of predicted defect concentrations, as a function of oxygen partial pressure, suggest that iron behaves as a p-type dopant in monoclinic ZrO 2 while it binds strongly to oxygen vacancies in tetragonal ZrO 2. Analysis of defect relaxation volumes suggest that these results should hold true in thermally grown oxides on zirconium, which is und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 64 publications
2
15
0
Order By: Relevance
“…The temperature used in this study is 1500 K (rather than the cladding operating temperature of about 600 K) since below this temperature the tetragonal phase is not stable without stress or doping. Previous studies [19,[33][34][35][36] that are based on similar simulation techniques have also taken this approach and have obtained results consistent with experiment. Furthermore, Bell [37] demonstrated the analogous effects of increased temperature and stress on the predicted defect concentrations.…”
Section: Methodsmentioning
confidence: 69%
See 4 more Smart Citations
“…The temperature used in this study is 1500 K (rather than the cladding operating temperature of about 600 K) since below this temperature the tetragonal phase is not stable without stress or doping. Previous studies [19,[33][34][35][36] that are based on similar simulation techniques have also taken this approach and have obtained results consistent with experiment. Furthermore, Bell [37] demonstrated the analogous effects of increased temperature and stress on the predicted defect concentrations.…”
Section: Methodsmentioning
confidence: 69%
“…Using the formation energies, Brouwer diagrams were generated with concentrations of 10 −4 units of dopant per ZrO 2 , which roughly corresponds to the amount of Fe, Cr, or Ni found in regions outside areas of elevated concentration in Zircaloy-2 and Zircaloy-4 cladding [20,28,45], bearing in mind that the solute solubilities would be lower. It has also been previously shown that identification of dominant defect species is not very sensitive to the imposed dopant concentration during the construction of Brouwer diagrams [19].…”
Section: Methodsmentioning
confidence: 97%
See 3 more Smart Citations